SM-368229, a Novel Selective and Potent Non-steroidal Mineralocorticoid Receptor Antagonist With Strong Urinary Na+ Excretion Activity - Tetsuro Nariai; Katsuya Fujita; Masaya Mori; Seiji Katayama; Seiji Hori; Kazuki Matsui (Elsevier, 2011)
Mineralocorticoid receptor (MR) antagonists, such as spironolactone (SPI) and eplerenone (EPL), are useful for the treatment of hypertension and heart failure. However, the use of these two agents has been limited due to endocrine disturbance (SPI) and poor drug action (EPL). In our search for safer and more effective MR antagonists, we identified SM-368229 as a novel non-steroidal MR antagonist. SM-368229 showed strong MR inhibitory activity with IC50 values of 0.021 and 0.13 μM in the binding assay and reporter-gene assay, respectively. The selectivity of SM-368229 for MR was 18-fold higher than that for other steroid receptors, such as androgen, progesterone, and glucocorticoid receptors. SM-368229 dose-dependently increased urinary Na+/K+ ratio with an ED50 value of 5.6 mg/kg in adrenalectomized rats treated with deoxycorticosterone acetate, and its efficacy was superior to that of SPI (ED50 = 14 mg/kg) or EPL (ED50 = 147 mg/kg). Moreover, even at high doses of 100 and 300 mg/kg, SM-368229 showed very weak antiandrogenic effect in methyltestosterone-treated male rats and no progestagenic effect in estrus cycle synchronized female rats. These findings indicate that SM-368229 may offer a new promising therapeutic option for the treatment of hypertension and heart failure. Keywords:: mineralocorticoid receptor (MR), aldosterone, spironolactone, eplerenone, steroid hormone